The Problem of Transfer Pricing in Indonesia Taxation System - Huda, Mokhamad Khoirul; Nugraheni, Ninis; Kamarudin, Kamarudin (International Journal of Economics and Financial Issues, 2017)
This paper aims to analyze Indonesia taxation system in term of transfer pricing transaction held by multinational enterprises cooperating with affiliated ones overseas. As the consequence of transfer pricing, the government has a decreasing potential income from tax, since those multinational companies are more likely to shift their tax liabilities into other countries with lower tax rate. The practice of transfer pricing commonly happens as a form of minimizing tax expense by making use the loopholes of tax provision without disobeying any taxation rules (tax avoidance) and the transaction in order to minimize the payable tax liabilities by disobeying any tax provision (tax evasion). Transfer pricing is held by multinational companies in order to minimize their operating performance and optimize the tax arrangements as either as the main or important priority. Keywords: transfer pricing, multinational enterprise, taxation system, Indonesia. JEL Classifications: H2, L1